Multimodality Imaging of Chronic Ischemia. (7th October 2010) - Ishikawa, Kiyotake; Ladage, Dennis; Rapti, Kleopatra; Fernandez-Friera, Leticia; Maria Garcia-Lopez, Ana; Sanz, Javier; Hajjar, Roger J.; Kawase, Yoshiaki; Garcia, Mario J.
Abstract : Although ischemic cardiomyopathy is commonly caused by chronic obstructive coronary disease, the mechanism of the cause is still under investigation. We present echocardiographic strain, magnetic resonance, and histology findings in a chronic ischemia model in preclinical study. This case illustrates the features of multimodality imaging in chronic obstructive coronary disease and gives us great insight into understanding the mechanism of ischemic cardiomyopathy.